2017
DOI: 10.1371/journal.pone.0178577
|View full text |Cite
|
Sign up to set email alerts
|

Population-based incidence, seasonality and serotype distribution of invasive salmonellosis among children in Nanoro, rural Burkina Faso

Abstract: BackgroundBloodstream infections (BSI) caused by Salmonella Typhi and invasive non-Typhoidal Salmonella (iNTS) frequently affect children living in rural sub-Saharan Africa but data about incidence and serotype distribution are rare.ObjectiveThe present study assessed the population-based incidence of Salmonella BSI and severe malaria in a Health and Demographic Surveillance System in a rural area with seasonal malaria transmission in Nanoro, Burkina Faso.MethodsChildren between 2 months—15 years old with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 35 publications
2
40
1
1
Order By: Relevance
“…Similar to the results presented in this study, the Typhimurium-to-Enteritidis ratio varied between 1:1 to 1:8 between countries [44]. Variations in serotype distribution over time or between centers have been recently described in Malawi, Burkina Faso and Mali [45][46][47].…”
Section: Comparison With Other Sub-saharan African Countriessupporting
confidence: 88%
“…Similar to the results presented in this study, the Typhimurium-to-Enteritidis ratio varied between 1:1 to 1:8 between countries [44]. Variations in serotype distribution over time or between centers have been recently described in Malawi, Burkina Faso and Mali [45][46][47].…”
Section: Comparison With Other Sub-saharan African Countriessupporting
confidence: 88%
“…Among 13,303 confirmed typhoid cases from studies reporting mortality, 250 died, for a CFR of 1.9% ( Table 3) Sixty-seven (84.8%) of 79 non-surgical study sites were hospital-based, and 12 (15.2%) were population or community-based studies. 37,38,60,73,84,90,96,118 Ten (83.3%) of 12 non-hospital study sites were located in Asia and two (16.7%) in Africa; one each in Kenya 37 and Burkina Faso. 60 No deaths were reported among 866 confirmed typhoid cases in the 12 non-hospital sites compared to 250 (2.0%) of 12,437 hospital-based confirmed cases (Χ 2 =16.7; p<0.01).…”
Section: Typhoid Fever Mortalitymentioning
confidence: 99%
“…Fifteen studies (34.1%) used blood film microscopy to test 10,451 participants for malaria and identified parasitemia in 4,301 (41.2%) (31,32,35,36,38,40,41,43,45,46,(60)(61)(62)(63)(64)(65). Eight studies reported malaria and BSI coinfection (31,32,43,45,(61)(62)(63)65 (62,65).…”
Section: Community-onset Bloodstream Infections Antimicrobial Agents mentioning
confidence: 99%
“…Fifteen studies (34.1%) used blood film microscopy to test 10,451 participants for malaria and identified parasitemia in 4,301 (41.2%) (31,32,35,36,38,40,41,43,45,46,(60)(61)(62)(63)(64)(65). Eight studies reported malaria and BSI coinfection (31,32,43,45,(61)(62)(63)65 (62,65). Twelve (27.3%) studies with 8,109 participants tested patients for HIV using either serological or nucleic acid amplification methods and described BSI coinfection (32,33,35,36,40,41,48,61,62,65,67,69).…”
Section: Community-onset Bloodstream Infections Antimicrobial Agents mentioning
confidence: 99%